Isokinetic imbalance of hip muscles in soccer players with osteitis pubis - Mohammad, W. S.; Abdelraouf, O. R.; Elhafez, S. M.; Abdel-Aziem, A. A.; Nassif, N. S. (Journal of Sports Sciences, 2014)
In this study, we compared the isokinetic torques of hip flexors/extensors and abductors/adductors in soccer players suffering from osteitis pubis (OP), with normal soccer players. Twenty soccer male athletes with OP and 20 normal soccer athletes were included in this study. Peak torque/body weight (PT/BW) was recorded from hip flexor/extensor and abductor/adductor muscles during isokinetic concentric contraction modes at angular velocity of 2.1 rad/s, for both groups. The results showed a significant difference between the normal and OP groups for hip flexors (P < 0.05). The normal group had significant, lower PT/BW value than the OP group for their hip flexors (P < 0.05). The hip flexor/extensor PT ratio of OP affected and non-affected limbs was significantly different from that of normal dominant and non-dominant limbs. There were no significant differences between the normal and OP groups for hip extensor, adductor and abductor muscles (P > 0.05). Regarding the hip adductor/abductor PT ratio, there was no significant difference between the normal and OP groups of athletes (P > 0.05). The OP group displayed increase in hip flexor strength that disturbed the hip flexor/extensor torque ratio of OP. Therefore, increasing the hip extensor strength should be part of rehabilitation programmes of patients with OP.